Problem-based learning interactive multimedia to optimize elementary school natural and social sciences learning - Praja, Insania Rizkyning; Andriani, Aldina Eka (Universitas Islam Negeri Raden Intan Lampung, 2025)
Teachers have not yet optimally utilized technology-based learning media within the problem-based learning (PBL) model, resulting in low problem-solving abilities among students and poor academic achievement in natural and social sciences. This study aims to describe the development design, assess feasibility, and evaluate the effectiveness of PBL-based interactive multimedia in improving student learning outcomes. This research employed the research and development method using the ADDIE development model. Data collection techniques involved test and non-test methods, while data analysis included normality tests, t-tests, and N-Gain tests. The findings indicate that PBL-based interactive multimedia is highly feasible, with feasibility ratings of 95% from subject matter experts, 93.75% from media experts, 98.75% from teachers, and 95% from students. The effectiveness of this multimedia was supported by t-test results, which yielded Sig. (2-tailed) = 0.000 < 0.05, and an N-Gain score of 0.7350, classified as high. Thus, the developed PBL-based interactive multimedia is feasible and effective in enhancing learning outcomes for phase changes of matter among fourth-grade students at SDN Ngaliyan 05 Kota Semarang. This study implies the development of interactive multimedia, which enhances students’ problem-solving skills and facilitates teachers in integrating technology effectively into learning.